Identification and Control of Occupational Hazards in Recycled Paper Production Using the HIRADC Method - Dyah Setyo Pertiwi; Trinita Septiani Putri; Khairunnisa Fitri Maryam; Riny Yolandha Parapat (PT Ilmu Data Indonesia, 2026)
The recycled paper manufacturing industry involves various production stages that may expose workers to occupational hazards. This study aims to identify potential hazards, assess risk levels, and determine appropriate control measures in the production of recycled paper (Samson kraft) using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. Data were collected through direct observation, interviews with production workers and laboratory personnel, and documentation of production activities. Hazard identification was conducted in all production stages, including raw material storage and pressing, hydropulping, stock preparation, paper machine operations (wire part, press part, and dryer part), calendering, pope reel operations, and wastewater treatment. The results identified 24 potential hazards categorized as physical, mechanical, chemical, ergonomic, environmental, electrical, and biological hazards. Risk assessment indicated that Very High risks were concentrated in hydropulping, press part, dryer part, and calendering operations due to rotating machinery entrapment and exposure to high-temperature steam. High risks were associated with slippery floors, noise exposure, chemical handling, and material handling activities, while medium risks were mainly related to ergonomic strain and low-level chemical exposure. Evaluation of existing controls showed that risk mitigation measures were primarily based on administrative controls and personal protective equipment (PPE), whereas engineering controls remained limited in several critical areas. Residual risk assessment demonstrated that risk levels decreased after implementing proposed controls; however, several hazards remained at medium risk levels. Therefore, strengthening engineering controls, safety training, and safety culture is necessary to improve occupational safety performance in recycled paper manufacturing facilities.